FICTION IN GENERALIST AMERICAN TELEVISION AND REPRESENTATION OF (NEW) MASCULINITIES - Zurian Hernandez, Francisco A.; Martinez Avila, Daniel [UNESP]; Gomez Prada, Hernando C. (Univ Complutense Madrid, Servicio Publicaciones, 2015)
The text offers a tour through different representations of male characters in American generalist television that are beyond the classical representation of the male characters that were depicted as traditionally strong characters, courageous and machos. Considering how American television fiction has a maximum expansion -not only in the US but, also for its strong presence in all Western television, in Spain-we could see the impact that these representations can make in the public in order to build new identitarian points of reference of the masculine, masculinity and virility.
Keywords: Masculinity; Men; Audiovisual Gender; Aesthetics